Suwanee Lumber Company - Elias, Jaan, (SAGE Business cases., 2020)
In 2016, Blue Wolf, a private equity firm headquartered in New York City, confronted a number of options when it came to its lumber business. They could put their holdings in the Suwanee Lumber Company (SLC), a sawmill they had purchased in 2013, up for sale. Or they could continue to hold onto SLC and run it as a standalone business. Or they could double down on the lumber business by buying an idle mill in Arkansas to run along with SLC.